The Satisfaction Analysis of Airport Services - Darius Angtony; Andri Irfan Rifai; Indrastuti Indrastuti (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: Hang Nadim Airport is the only airport in Batam. And recently, Hang Nadim Airport closed some of their flight route. This cause less plane to fly, and will increase the potential of flight delays. Flight rescheduling can be main reason of dissatisfaction. But besides that, this paper will also focus on check-in service speed, check-in hospitality, comfortability, security, hygiene, food & beverages, providing accurate information, pricing, online services, and facilities provided for the indicators on service satisfaction. The method used in this research is Interpretative phenomenological analysis (IPA). The data obtained are: Hang Nadim Airport needs to improve on providing accurate information about departure and arrival time and facilities, food & beverages; pricing; and online services are the lowest priority at Hang Nadim Airport, and check-in service speed; check-in hospitality; comfortability; security; and hygiene is where Hang Nadim Airport needs to keep up the good work. Design/methodology/approach: Analyzing data collected from Interpretative Phenomenological Analysis (IPA) questionnaire. Findings: Indicators that need to be improved, or keep up for Hang Nadim Airport. This way, they can give satisfying service towards passengers. Research limitations/implications: This paper is very limited on sample size. We were only able to collect total of 109 respondents, which is very small compared to Hang Nadim Airport user. Practical implications: Giving inputs toward Hang Nadim Airport many indicators to be improved, or keep up, in hope it will be implemented in the future. Originality/value: The analysis process of this research paper is originally made by authors and purely based on research and study. Paper type: Research paper.